A water-based anticorrosive coating based on aluminum alloy substrate and its preparation process

By using components such as aqueous acrylic modified epoxy alkyd resin in aqueous anticorrosion coatings, chemical bonds and mechanical interlocking are formed, the problem of insufficient surface bonding between existing coatings and aluminum alloys is solved, and the adhesion and corrosion resistance of the coating are significantly improved.

CN119505625BActive Publication Date: 2025-04-11SHANXI LVJIAN ZHIZAO DECORATIVE ALUMINUM PLATE TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510081186.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-11
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The existing water-based anticorrosion coatings have weak bonding power and aluminum alloy surfaces and have poor mechanical properties, which leads to the coating being easily disengaged after film formation and cannot effectively protect aluminum alloy materials.

Method used

Using aqueous anticorrosion coatings based on the aluminum alloy base layer, the preparation raw materials include aqueous acrylic modified epoxy alkyd resin, inorganic nanomaterials, polydimethylsiloxane and ethoxymodified polytrisiloxane. Through the combination of these components, chemical bonds and mechanical interlocking are formed to improve adhesion and mechanical properties.

Benefits of technology

It significantly improves the bonding and mechanical properties of water-based anticorrosion coatings and aluminum alloy surfaces, enhances the adhesion and corrosion resistance of the coatings, and extends the service life of aluminum alloy materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505625B_ABST
    Figure CN119505625B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of anticorrosive coatings, and specifically discloses a water-based anticorrosive coating based on an aluminum alloy base and a preparation process thereof. A water-based anticorrosive coating based on an aluminum alloy base, in parts by weight, the raw materials for preparing the water-based anticorrosive coating include the following components: 55-70 parts of water-based acrylic modified epoxy alkyd resin, 4-10 parts of dioctyl phosphate acyloxy titanate, 15-24 parts of inorganic nanomaterials, 1-3 parts of polydimethylsiloxane, 2-6 parts of ethoxy-modified polytrisiloxane, 2-5 parts of passivator and 70-120 parts of water. The water-based anticorrosive coating in this application has the advantages of corrosion resistance, strong adhesion and good mechanical properties, and can play a stable protective role and extend its service life when applied to the surface of the aluminum alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of anti-corrosion coatings, and in particular to a water-based anti-corrosion coating based on an aluminum alloy substrate and a preparation process thereof. Background Art

[0002] Aluminum alloys are widely used due to their high strength, easy processing and light weight. In the field of construction, aluminum alloys are often used in the production of building components such as doors, windows, curtain walls, and ceilings. Although an oxide film will form on the surface of aluminum alloys, which can block some erosion caused by environmental factors, its service life is short and will pose a great threat to the stability of the building.

[0003] Coating water-based anti-corrosion coatings on the surface of aluminum alloy materials is a way to protect aluminum alloy materials from corrosion as much as possible under extreme environmental conditions. Water-based anti-corrosion coatings have low volatile organic compound content, low odor, and are more environmentally friendly. They are currently widely used.

[0004] However, the performance of existing water-based anti-corrosion coatings is still not perfect. Some water-based anti-corrosion coatings have weak bonding with the surface of aluminum alloy materials and poor mechanical properties, which causes the water-based anti-corrosion coatings to easily separate from the surface of aluminum alloy materials after film formation, and fail to protect the aluminum alloy materials, thus affecting the service life of the aluminum alloy materials. Summary of the invention

[0005] In order to enhance the bonding strength between water-based anti-corrosion coatings and the surface of aluminum alloy materials and improve their mechanical properties, the present application provides a water-based anti-corrosion coating based on an aluminum alloy base layer and a preparation process thereof.

[0006] In the first aspect, the present application provides a water-based anti-corrosion coating based on an aluminum alloy substrate, which adopts the following technical solution:

[0007] A water-based anti-corrosion coating based on an aluminum alloy substrate. The raw materials for preparing the water-based anti-corrosion coating include the following components in parts by weight: 55-70 parts of water-based acrylic modified epoxy alkyd resin, 4-10 parts of dioctyl phosphate acyloxy titanate, 15-24 parts of inorganic nanomaterials, 1-3 parts of polydimethylsiloxane, 2-6 parts of ethoxy-modified polytrisiloxane, 2-5 parts of a passivator and 70-120 parts of water.

[0008] By adopting the above technical scheme, the water-based acrylic modified epoxy alkyd resin combines the advantages of acrylic resin, epoxy resin and alkyd resin, and has good film-forming property, adhesion, flexibility, corrosion resistance and weather resistance. The epoxy groups in the water-based acrylic modified epoxy alkyd resin can react with the oxides on the surface of the aluminum alloy to form chemical bonds, thereby enhancing the adhesion between the coating and the surface of the aluminum alloy. Moreover, the water-based acrylic modified epoxy alkyd resin will form a coating with a certain roughness after the coating is cured, which can form a mechanical interlocking effect with the surface of the aluminum alloy, thereby further improving the adhesion between the coating and the surface of the aluminum alloy.

[0009] Dioctylphosphoacyloxy titanate will react with the epoxy groups in the waterborne acrylic modified epoxy alkyd resin to form a stable network structure, which improves the mechanical properties and corrosion resistance of the coating. Inorganic nanomaterials can interact with the polar groups in the waterborne acrylic modified epoxy alkyd resin to form a strong interfacial bonding force and improve the overall performance of the coating. Polydimethylsiloxane can improve the fluidity of the coating so that the coating can be evenly coated on the surface of the aluminum alloy. Ethoxy-modified polytrisiloxane can improve the dispersibility of other ingredients, reduce the surface tension of the coating, and help the coating to better wet the surface of the aluminum alloy, thereby improving the bonding and adhesion of the coating on the surface of the aluminum alloy. The combination of polydimethylsiloxane and ethoxy-modified polytrisiloxane can further improve the adhesion of the coating on the surface of the aluminum alloy, improve the uniformity and smoothness of the coating, and reduce the possibility of coating damage.

[0010] In the present application, the passivating agent is selected from one or more of calcium nitrate, sodium molybdate, zinc molybdate, ammonium molybdate, fluorotitanic acid, zinc phosphate, sodium tripolyphosphate, aluminum tripolyphosphate, calcium phosphate and calcium hydrogen phosphate.

[0011] Preferably, the mass ratio of the polydimethylsiloxane to the ethoxy-modified polytrisiloxane is 1:(1-3).

[0012] By adopting the above technical solution, the mass ratio of polydimethylsiloxane and ethoxy-modified polytrisiloxane is further adjusted, which helps to improve the fluidity of the coating, reduce the surface tension of the coating, and increase the adhesion of the coating, so that it can be evenly bonded to the aluminum alloy surface.

[0013] In some preferred embodiments, the mass ratio of the polydimethylsiloxane to the ethoxy-modified polytrisiloxane may be 1:1, 1:2, or 1:3.

[0014] Preferably, the waterborne acrylic acid modified epoxy alkyd resin is prepared by the following steps:

[0015] A1. Mix 25-35 parts of coconut oleic acid, 6-11 parts of epoxy resin and 0.5-1 part of zinc carbonate, raise the temperature to 170-190°C and react for 1-3 hours to obtain a mixed solution A;

[0016] A2, add 1-3 parts of xylene, 4-6 parts of benzoic acid, 11-15 parts of pentaerythritol and 10-13 parts of phthalic anhydride to the mixed solution A, mix well and heat to 200-220° C., react until the acid value is less than 10 mgKOH / g, add 12-20 parts of ethylene glycol butyl ether after cooling, mix well to obtain a mixed solution B;

[0017] A3, 3-5 parts of styrene, 8-12 parts of methyl methacrylate, 2-4 parts of acrylic acid, 1-2.5 parts of butyl acrylate and 0.5-1 part of benzoyl peroxide are uniformly mixed to obtain a mixed solution C;

[0018] A4. Add the mixed solution C into 30-40 parts of mixed solution B, heat to 120-130° C. and mix evenly, react for 1-2 hours, add 0.1-0.5 parts of tert-butyl hydroperoxide, continue to react for 1-2 hours, cool, adjust the pH to 7-9, and obtain the waterborne acrylic modified epoxy alkyd resin.

[0019] By adopting the above technical scheme, the prepared water-based acrylic modified epoxy alkyd resin combines the advantages of epoxy resin, alkyd resin and acrylic resin, has good film-forming properties, adhesion, flexibility, corrosion resistance and weather resistance, and is used in water-based anti-corrosion coatings to greatly improve the overall performance of the coatings.

[0020] Preferably, the inorganic nanomaterial includes nano zinc oxide and silicon carbide molecular sieve.

[0021] By adopting the above technical scheme, silicon carbide molecular sieve has excellent high temperature resistance, corrosion resistance and wear resistance, while nano zinc oxide can form a dense protective film on the surface of the coating, which has antibacterial, UV protection, corrosion reduction and other properties. Both have good adhesion, and silicon carbide molecular sieve has a hydrophilic surface property, which can interact with water molecules in water-based coatings and has good compatibility, which helps to reduce the agglomeration of nano zinc oxide and improve the dispersibility of nano zinc oxide. The two are used in combination to further enhance the adhesion of the coating on the surface of aluminum alloy.

[0022] Preferably, the mass ratio of the nano zinc oxide to the silicon carbide molecular sieve is (3-7):1.

[0023] By adopting the above technical solution, the mass ratio of nano zinc oxide and silicon carbide molecular sieve is controlled within the above range, which helps to improve the dispersibility of nano zinc oxide in the coating, thereby forming a uniform and dense protective film on the coating surface and improving the overall performance of the coating.

[0024] In some preferred embodiments, the mass ratio of the nano zinc oxide to the silicon carbide molecular sieve can be 3:1, 5:1 or 7:1, etc.

[0025] As a preference, 1-3 parts of borane triethylamine are also added.

[0026] By adopting the above technical solution, borane triethylamine can form a strong chemical bond with the surface of the aluminum alloy, improve the adhesion between the coating and the aluminum alloy surface, and help reduce the possibility of coating shedding and peeling. In addition, borane triethylamine can form a stable complex with certain groups in dioctyl phosphate acyloxy titanate, thereby improving the stability of dioctyl phosphate acyloxy titanate and further improving the overall performance of the coating.

[0027] Preferably, the mass ratio of the borane triethylamine to dioctylphosphoacyloxytitanate is 1:(2-6).

[0028] By adopting the above technical solution, the mass ratio of borane triethylamine to dioctyl phosphate titanate is further adjusted, which helps to improve the stability of dioctyl phosphate titanate and thus enhance the mechanical properties of the coating.

[0029] In some preferred embodiments, the mass ratio of the borane triethylamine to dioctylphosphoacyloxytitanate may be 1:2, 1:3, 1:4 or 1:6, etc.

[0030] In the second aspect, the present application provides a preparation process of a water-based anti-corrosion coating based on an aluminum alloy substrate, using the following technical solution:

[0031] A preparation process of a water-based anti-corrosion coating based on an aluminum alloy substrate comprises the following steps:

[0032] S1, mixing the water-based acrylic acid modified epoxy alkyd resin and water uniformly to prepare a premixed liquid;

[0033] S2. Evenly mix the premixed liquid, dioctylphosphoacyloxytitanate, inorganic nanomaterials, polydimethylsiloxane, ethoxy-modified polytrisiloxane and other raw materials to prepare a water-based anticorrosive coating.

[0034] In summary, the present application includes at least one of the following beneficial technical effects:

[0035] 1. Introducing epoxy groups and acrylic resin components into the molecular structure of alkyd resin, the water-based acrylic modified epoxy alkyd resin has good film-forming properties, adhesion, flexibility, corrosion resistance and weather resistance. The epoxy groups can also react with the oxides on the surface of aluminum alloy, thereby improving its adhesion.

[0036] 2. Polydimethylsiloxane can improve the fluidity of the coating, and ethoxy-modified polytrisiloxane can improve the dispersibility of polydimethylsiloxane in the coating and reduce the surface tension of the coating. The combination of the two enables the coating to better wet the surface of the aluminum alloy, thereby evenly coating the surface of the aluminum alloy to form a smooth coating;

[0037] 3. The coating of the present application contains an inorganic nanomaterial compounded of nano zinc oxide and silicon carbide molecular sieve, wherein the nano zinc oxide can form a dense oxide film on the surface of the coating, and the silicon carbide molecular sieve, in addition to having high temperature resistance, corrosion resistance and wear resistance, can also improve the dispersibility of nano zinc oxide, so that it can be evenly distributed in the coating, further improving the corrosion resistance and mechanical properties of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a flow chart of a method for preparing a water-based acrylic acid-modified epoxy alkyd resin in a water-based anticorrosive coating of the present application;

[0039] Figure 2 This is a flow chart of the preparation method of the water-based anti-corrosion coating of the present application. DETAILED DESCRIPTION

[0040] In order to make the present application easier to understand, the present application will be further described in detail below in conjunction with the examples, which are merely illustrative and are not intended to limit the scope of application of the present application. The raw materials or components used in the present application can be obtained through commercial routes or conventional methods unless otherwise specified.

[0041] Source of raw materials

[0042] Polydimethylsiloxane, CAS number is 9006-65-9, the active ingredient content is 99%; ethoxy modified polytrisiloxane, model is LBW-5983, the active ingredient content is 99%; epoxy resin model is EP137, the active ingredient content is 98%.

[0043] Preparation Example 1:

[0044] Reference Figure 1 The preparation method of the water-based acrylic acid modified epoxy alkyd resin in Preparation Example 1 is as follows:

[0045] A1. Mix 30 kg of coconut oleic acid, 8 kg of epoxy resin and 0.8 kg of zinc carbonate evenly, heat to 180 °C and react for 2 h to obtain a mixed solution A;

[0046] A2, add 2kg of xylene, 5kg of benzoic acid, 13kg of pentaerythritol and 12kg of phthalic anhydride to the mixed solution A, mix well, heat to 210°C, cool when the acid value is detected to be less than 10mgKOH / g, add 16kg of ethylene glycol butyl ether after cooling, mix well to obtain a mixed solution B;

[0047] A3, 4 kg of styrene, 10 kg of methyl methacrylate, 3 kg of acrylic acid, 1.5 kg of butyl acrylate and 0.5 kg of benzoyl peroxide were uniformly mixed to obtain a mixed solution C;

[0048] A4. Add all the mixed solution C prepared in step A3 into 35 kg of mixed solution B, heat to 120°C and mix evenly, react for 1 hour, add 0.3 kg of tert-butyl hydroperoxide, continue to react for 1 hour, cool, adjust the pH to 7, and obtain a water-based acrylic modified epoxy alkyd resin.

[0049] Preparation Example 2:

[0050] The preparation method of the water-based acrylic acid modified epoxy alkyd resin in Preparation Example 2 is as follows:

[0051] A1. Mix 25 kg of coconut oleic acid, 11 kg of epoxy resin and 1 kg of zinc carbonate evenly, heat to 170°C and react for 3 hours to obtain a mixed solution A;

[0052] A2, add 1kg of xylene, 6kg of benzoic acid, 11kg of pentaerythritol and 13kg of phthalic anhydride to the mixed solution A, mix well, heat to 200°C, cool when the acid value is detected to be less than 10mgKOH / g, add 12kg of ethylene glycol butyl ether after cooling, mix well to obtain a mixed solution B;

[0053] A3, 3 kg of styrene, 12 kg of methyl methacrylate, 2 kg of acrylic acid, 2.5 kg of butyl acrylate and 0.5 kg of benzoyl peroxide were uniformly mixed to obtain a mixed solution C;

[0054] A4. Add all the mixed solution C prepared in step A3 into 30 kg of mixed solution B, heat to 120°C and mix evenly, react for 1 hour, add 0.1 kg of tert-butyl hydroperoxide, continue to react for 1 hour, cool, adjust the pH to 8, and obtain a water-based acrylic modified epoxy alkyd resin.

[0055] Preparation Example 3:

[0056] The preparation method of the water-based acrylic acid modified epoxy alkyd resin in Preparation Example 3 is as follows:

[0057] A1. Mix 35 kg of coconut oleic acid, 6 kg of epoxy resin and 0.5 kg of zinc carbonate evenly, heat to 190° C. and react for 1 hour to obtain a mixed solution A;

[0058] A2, add 3kg of xylene, 4kg of benzoic acid, 15kg of pentaerythritol and 10kg of phthalic anhydride to the mixed solution A, mix well, heat to 220°C, cool when the acid value is detected to be less than 10mgKOH / g, add 20kg of ethylene glycol butyl ether after cooling, mix well to obtain a mixed solution B;

[0059] A3, 5 kg of styrene, 8 kg of methyl methacrylate, 4 kg of acrylic acid, 1 kg of butyl acrylate and 1 kg of benzoyl peroxide were uniformly mixed to obtain a mixed solution C;

[0060] A4. Add all the mixed solution C prepared in step A3 into 40 kg of mixed solution B, heat to 130°C and mix evenly, react for 2 hours, add 0.5 kg of tert-butyl hydroperoxide, continue to react for 2 hours, cool, adjust the pH to 9, and obtain a water-based acrylic modified epoxy alkyd resin.

[0061] Preparation Example 4:

[0062] The preparation method of the water-based acrylic acid modified epoxy alkyd resin in Preparation Example 4 is as follows:

[0063] 10 kg of waterborne acrylic resin, 6 kg of waterborne epoxy resin, 25 kg of waterborne alkyd resin, 3 kg of vinyl triethoxysilane and 12 kg of water were uniformly mixed to prepare a waterborne acrylic modified epoxy alkyd resin.

[0064] Embodiment 1-3:

[0065] The raw materials and dosages of the water-based anti-corrosion coatings of Examples 1-3 are shown in Table 1, wherein the water-based acrylic modified epoxy alkyd resin is selected from the water-based acrylic modified epoxy alkyd resin prepared in Preparation Example 1, the inorganic nanomaterials include nano zinc oxide and silicon carbide molecular sieve, the mass ratio of nano zinc oxide and silicon carbide molecular sieve is 5:1, and the mass ratio of polydimethylsiloxane and ethoxy-modified polytrisiloxane is 1:2.

[0066] Reference Figure 2 The preparation method of the water-based anti-corrosion coating is as follows: S1. Evenly mix the water-based acrylic modified epoxy alkyd resin and water to obtain a premixed liquid; S2. Evenly mix the premixed liquid, dioctyl phosphate titanate, inorganic nanomaterials, polydimethylsiloxane, ethoxy-modified polytrisiloxane and other preparation raw materials to obtain a water-based anti-corrosion coating.

[0067] Embodiment 4-5:

[0068] The raw materials and dosages of the water-based anti-corrosion coatings of Example 4-5 are shown in Table 1. The difference between Example 4-5 and Example 1 is that the dosage of ethoxy-modified polytrisiloxane is different. The mass ratios of polydimethylsiloxane and ethoxy-modified polytrisiloxane in Example 4-5 are 1:1 and 1:3, respectively, and the rest are the same as Example 1.

[0069] Embodiment 6-7:

[0070] The raw materials and dosages of the water-based anti-corrosion coatings of Examples 6-7 are shown in Table 1. The difference between them and Example 1 is that the dosages of nano zinc oxide and silicon carbide molecular sieve in the inorganic nanomaterials are different. The mass ratios of nano zinc oxide and silicon carbide molecular sieve in Examples 6-7 are 3:1 and 7:1, respectively, and the rest are the same as Example 1.

[0071] Table 1. Raw materials and dosage of water-based anticorrosive coatings in Examples 1-7 (kg)

[0072]

[0073] Embodiment 8-11:

[0074] The raw materials and dosages of the water-based anti-corrosion coatings of Examples 8-11 are shown in Table 2. The difference from Example 1 is that borane triethylamine is also added. The mass ratios of borane triethylamine to dioctyl phosphate titanate in Examples 8-11 are 1:6, 1:4, 1:3 and 1:2, respectively, and the rest are the same as Example 1.

[0075] Table 2. Raw materials and dosages of water-based anticorrosive coatings in Examples 8-11 (kg)

[0076]

[0077] Embodiment 12-14:

[0078] The difference between Examples 12-14 and Example 10 is that the water-based acrylic acid-modified epoxy alkyd resins are respectively selected from the water-based acrylic acid-modified epoxy alkyd resins prepared in Preparation Examples 2-4, and the rest is the same as Example 10.

[0079] Comparative Example 1:

[0080] The difference between Comparative Example 1 and Example 1 is that the amount of polydimethylsiloxane added is 0 kg, the amount of ethoxy-modified polytrisiloxane added is 6 kg, and the rest is the same as Example 1.

[0081] Comparative Example 2:

[0082] The difference between Comparative Example 2 and Example 1 is that the amount of polydimethylsiloxane added is 6 kg, the amount of ethoxy-modified polytrisiloxane added is 0, and the rest is the same as Example 1.

[0083] Comparative Example 3:

[0084] The difference between Comparative Example 3 and Example 1 is that the inorganic nano material is 18 kg of nano zinc oxide, and the rest is the same as Example 1.

[0085] Comparative Example 4:

[0086] The difference between Comparative Example 4 and Example 1 is that the inorganic nanomaterial is 18 kg of silicon carbide molecular sieve, and the rest is the same as Example 1.

[0087] Test example:

[0088] The water-based anti-corrosion coatings prepared in Examples 1-14 and Comparative Examples 1-4 were subjected to performance tests, specifically including adhesion, salt spray resistance and flexibility tests, wherein the adhesion test was referred to GB / T 1720-2020 "Paint film scratch test", the salt spray resistance test was referred to GB / T 1771-2007 "Determination of neutral salt spray resistance of paints and varnishes", and the flexibility test was referred to GB / T 1731-2020 "Determination of flexibility of paint films and putty films". The specific test results are shown in Table 3.

[0089] Table 3

[0090]

[0091] It can be seen from the test data in Table 3 that the water-based anti-corrosion coatings prepared in Examples 1-14 and Comparative Examples 1-4 have an adhesion of 1-3 levels, a salt spray corrosion resistance of 3960-8760 hours, and a flexibility of 1-3 mm.

[0092] It can be seen from the test data of Examples 1-3 that the water-based anti-corrosion coating prepared according to the raw materials and their dosages in Example 1 has better corrosion resistance and can better protect aluminum alloy materials.

[0093] It can be seen from the test data of Examples 1, 4-5 and Comparative Examples 1-2 that when the mass ratio of polydimethylsiloxane and ethoxy-modified polytrisiloxane is 1:1-1:3, it helps to improve the fluidity of the water-based anti-corrosion coating, reduce the surface tension of the water-based anti-corrosion coating, and increase the adhesion of the water-based anti-corrosion coating, so that the coating can be evenly and tightly coated on the aluminum alloy surface.

[0094] It can be seen from the test data of Examples 1, 6-7 and Comparative Examples 3-4 that when the mass ratio of nano zinc oxide and silicon carbide molecular sieve is 5:1, the two can be evenly dispersed in the coating to form a uniform and dense protective film on the coating surface, thereby improving the overall performance of the coating.

[0095] It can be seen from the test data of Examples 1 and 8-11 that adding borane triethylamine to the coating can significantly improve its overall performance, especially when the mass ratio of borane triethylamine to dioctyl phosphate titanate is 1:3, the stability of the coating can be improved, thereby enhancing the performance of the coating.

[0096] It can be seen from the test data of Examples 10 and 12-14 that the water-based acrylic modified epoxy alkyd resin prepared according to Preparation Example 1 has better performance. Adding it to the water-based anti-corrosion coating can improve the adhesion, salt spray corrosion resistance and flexibility of the coating, and extend the service life of the aluminum alloy material.

[0097] It should be noted that the embodiments described above are only used to explain the present application and do not constitute any limitation to the present application. The present application is described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present application may be modified as specified within the scope of the claims of the present application, and the present invention may be revised without departing from the scope and spirit of the present application. Although the present application described therein relates to specific methods, materials and embodiments, it does not mean that the present application is limited to the specific examples disclosed therein. On the contrary, the present application can be extended to all other methods and applications with the same functions.

Claims

1. A water-based anti-corrosion coating based on an aluminum alloy substrate, characterized in that: The raw materials for preparing the water-based anticorrosive coating include the following components by weight: 55-70 parts of water-based acrylic modified epoxy alkyd resin, 4-10 parts of dioctyl phosphate acyloxy titanate, 15-24 parts of inorganic nanomaterials, 1-3 parts of polydimethylsiloxane, 2-6 parts of ethoxy-modified polytrisiloxane, 2-5 parts of passivator and 70-120 parts of water; The waterborne acrylic acid modified epoxy alkyd resin is prepared by the following steps: A1. Mix 25-35 parts of coconut oleic acid, 6-11 parts of epoxy resin and 0.5-1 part of zinc carbonate, raise the temperature to 170-190°C and react for 1-3 hours to obtain a mixed solution A; A2, add 1-3 parts of xylene, 4-6 parts of benzoic acid, 11-15 parts of pentaerythritol and 10-13 parts of phthalic anhydride to the mixed solution A, mix well and heat to 200-220° C., react until the acid value is less than 10 mgKOH / g, add 12-20 parts of ethylene glycol butyl ether after cooling, mix well to obtain a mixed solution B; A3, 3-5 parts of styrene, 8-12 parts of methyl methacrylate, 2-4 parts of acrylic acid, 1-2.5 parts of butyl acrylate and 0.5-1 part of benzoyl peroxide are uniformly mixed to obtain a mixed solution C; A4, adding the mixed solution C to 30-40 parts of the mixed solution B, heating to 120-130° C. and mixing evenly, reacting for 1-2 hours, adding 0.1-0.5 parts of tert-butyl hydroperoxide, continuing the reaction for 1-2 hours, cooling, and adjusting the pH to 7-9 to obtain the waterborne acrylic acid modified epoxy alkyd resin; The inorganic nanomaterials include nano zinc oxide and silicon carbide molecular sieve.

2. The water-based anticorrosive coating based on an aluminum alloy substrate according to claim 1, characterized in that: The mass ratio of the polydimethylsiloxane to the ethoxy-modified polytrisiloxane is 1:(1-3).

3. The water-based anticorrosive coating based on an aluminum alloy substrate according to claim 1, characterized in that: The mass ratio of the nano zinc oxide to the silicon carbide molecular sieve is (3-7):

1.

4. The water-based anticorrosive coating based on an aluminum alloy substrate according to claim 1, characterized in that: 1-3 parts of borane triethylamine are also added.

5. The water-based anticorrosive coating based on an aluminum alloy substrate according to claim 4, characterized in that: The mass ratio of the borane triethylamine to dioctylphosphoacyloxy titanate is 1:(2-6).

6. A process for preparing a water-based anticorrosive coating as claimed in any one of claims 1 to 5, characterized in that: The steps include: S1, mixing the water-based acrylic acid modified epoxy alkyd resin and water uniformly to prepare a premixed liquid; S2. Evenly mix the premixed liquid, dioctylphosphoacyloxytitanate, inorganic nanomaterials, polydimethylsiloxane, ethoxy-modified polytrisiloxane and other raw materials to prepare a water-based anticorrosive coating.

Citation Information

Patent Citations

  • Waterborne alkyd resin with excellent abrasion resistance

    CN107916054A